MAKNA ISTILAH תֹהוּ וָבֹהוּ (TOHU WĀBŌHÛ) DALAM KEJADIAN 1:2: ANALISIS LEKSIKAL DAN TEOLOGIS TERHADAP KONSEP KEADAAN AWAL PENCIPTAAN - Aldi Pokkombong; Santiara; Presdiyono (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study examines the meaning of the Hebrew term תֹהוּ וָבֹהוּ (tohu wābōhû) in Genesis 1:2 through an integrative lexical and theological approach. Commonly translated as “formless and void,” this expression carries a deeper and more complex meaning within linguistic and Ancient Near Eastern cosmological contexts. The research employs a qualitative library-based method using exegetical analysis of the Hebrew text, supported by theological and historical-critical literature. The findings indicate that tohu conveys notions of disorder, non-functionality, and an unstructured condition, while bohu emphasizes emptiness or voidness. Together, they form an idiomatic expression describing the primordial state of the earth as unstructured reality, yet not absolute nothingness. In dialogue with Ancient Near Eastern cosmology, this concept shares similarities with the idea of primordial chaos, but differs theologically in that it is not personified as a force opposing God, rather it exists under His sovereignty. Theologically, tohu wābōhû bridges the understanding between creatio ex nihilo and creation as the ordering of chaos, affirming that creation involves both the act of bringing existence into being and the process of ordering it toward harmony. Thus, the term represents a potential state that becomes the object of God’s creative activity, while simultaneously affirming His sovereignty over all reality. This study contributes to a richer understanding of the doctrine of creation through a synthesis of linguistic analysis and theological reflection.